Socio-Semiotic Reading of Dangaura Tharu Folk Art Astimki in Western Nepal - Kharel, Megh Prasad (Journal of Durgalaxmi, 2025)
This paper emphasizes the socio-semiotic aspect of the Dangaura Tharu folk art that aims to explore the interconnection of myth, ritual, and symbol of particular ethnicity and its traditional type of cultural value. The folk art of Tharus is not an individual creation, but a composition and product of the socio-cultural rituality and practice for many generations. Indeed, such art has the emotional and cultural attachment of the entire Tharu community rather than a single folk creator and performer. Moreover, such art has shared identity as well as means to exist with a cultural heritage of the Tharu community. Likewise, the interconnected relationship of archetype, symbol, and ritual in Tharumural painting portrays the collective and social identity with the cultural context of the concerned ethnic group. On the one hand, this study seeks to examine how the mural painting Astimki of Dangaura Tharus represents the multiple facets of their narratives of myth as graphic pictures and lines of mural painting symbolize different local narratives of Tharus, such as Kānhā, Pancha Pando, Durpati, Gurbābā and creation myth, and Barmurwā. On the other hand, the investigation also spotlights how the performance of its ritualization of Tharu unmarried females (bathaniyā) during the period of Astimki festival enhances the continuity of the tradition of cultural heritage that reveals the strong marker of Tharus’ social identity and collective life. Consequently, local creative expression of Tharu mural painting and art opens up a new vista to the ritual followers and practitioners as well as other viewers in their locality.